2016
DOI: 10.1302/0301-620x.98b9.37140
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroscopy-guided reduction and fibular nail fixation to manage unstable ankle fractures in patients with diabetes

Abstract: Fluoroscopy-guided reduction and fibular nail fixation of unstable ankle fractures in patients with diabetes was associated with a low incidence of wound and overall complications, while providing effective surgical fixation. Cite this article: Bone Joint J 2016;98-B:1197-1201.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…There is mounting clinical evidence that intramedullary fibular nail fixation for unstable ankle fractures compares favorably to traditional plating techniques due to lower wound complication rates. [2][3][4]9,21,22,28 However, because of limited biomechanical evidence, some have questioned the strength of intramedullary fixation, especially in weaker, osteoporotic bone, and against a rotational force where historically intramedullary devices have failed. 23 A reproducible testing regime was designed incorporating a simulated cadaveric SER IV ankle fracture stressed in torque under a constant axial load.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is mounting clinical evidence that intramedullary fibular nail fixation for unstable ankle fractures compares favorably to traditional plating techniques due to lower wound complication rates. [2][3][4]9,21,22,28 However, because of limited biomechanical evidence, some have questioned the strength of intramedullary fixation, especially in weaker, osteoporotic bone, and against a rotational force where historically intramedullary devices have failed. 23 A reproducible testing regime was designed incorporating a simulated cadaveric SER IV ankle fracture stressed in torque under a constant axial load.…”
Section: Discussionmentioning
confidence: 99%
“…11,17 Recent clinical studies in diabetic and elderly patients with unstable ankle fractures have demonstrated that fibular nail fixation results in fewer wound complications and infections. 3,28 Furthermore, the fibular nail should have superior strength by virtue of its intramedullary location.…”
Section: Introductionmentioning
confidence: 99%
“…Within 22 publications that investigated fibular nail fixation, this implant was analyzed in 8 studies. 1,3,[6][7][8]11,22,29 The nail is made of titanium and allows secure cross-locking including distal anteroposterior locking screws and lateral to medial trans-implant tibial-fibular syndesmosis screws. This design allows fragment fixation in addition to fibular length and rotational stability.…”
Section: Historical Considerationsmentioning
confidence: 99%
“…The eventual amputation rate following deep infection was 13% (8% for closed fractures, 33% for open fractures). A retrospective case series in British Columbia (Canada) & Edinburgh (UK) published by Ashman et al 30 looked at the complication profile of the Acumed Fibula Rod System® (Acumed, New Jersey, USA) in 24 patients with diabetes deemed high risk (having HbA1c > 6.5 but without history of Charcot). They gave an overall wound infection rate of 8.3% which they compared to the current literature and found to be equivocal.…”
Section: Surgical Fixation (Supplementary Fixation or Alternative Fixation)mentioning
confidence: 99%